Fabrication And Characterizations Of Magnetron Co-Sputtered InAIN Films For Photodetectors Application - Afzal, Naveed (2017)
In this work, growth of indium aluminum nitride (InAlN) film was studied on different substrates by using reactive magnetron co-sputtering technique. The study was mainly focused to grow In-rich InAlN film on p-type Si (111) substrate with improved physical properties. The structural properties of InAlN were investigated through X-ray diffraction (XRD) analysis, surface properties were studied through field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM) whereas the electrical properties were examined by taking Hall measurements and current-voltage (I-V) characteristics of the films. The band gap of InAlN was estimated through UV-Vis reflectance spectroscopy.